Kearifan tempatan dalam cerita rakyat Dayak Kanayatn: Kajian Hermeneutik / Sesilia Seli - Sesilia , Seli (2016)
The folktales of Dayak Kanayatn are the representation of the various people’s ways of life. They represent the world view, moral teaching and any local wisdom, which are very important in building the state of mind of the young generation. Unfortunately, the number of people from this community who are interested to preserve their forktales are becoming less and less. Such a reality encourages the reseacher to preserve them by recording, documenting, and to study them intensively. This research focused on 16 stories of which they are categorized as gesah and singara. The objectives of this research are to analyse the aspects of local wisdom, to interprete the physical and spiritual symbols of the local wisdom, and to apply hermeneutics in analysing the local wisdom of Dayak Kanayatn community implied in the folktales. The researcher applied qualitative method and hermeneutics by Paul Riceour. The sorce of data is the folktales themselves. The data are in the forms of words, sentences, phrases, as well as paragraphs from the folktales. The data collection were conducted through field study and library research. The analysis and the interpretation is done by appliying the concept of symbol, context, local wisdom, and the theory of hermeneutics. The findings of this research show that the local knowledge, local values, technology and the local skills, local resources, the system of local decision making, and the local group solidarity. The interpretation of the physical symbols of the local wisdom has successfully interpreted nineteen symbols, they are long house, farm, the hut of paddy (dango padi), paddy, rice, the kids of leaves, sirih ( a kind of herbal leaf), farm hut (dango uma), paca’ basa’, hunted head (kepala kayau), weapon, agriculture, gasing, canoe, traditional food, forest, enggang (local bird), pig, mause, parakeet, as well as keto’, buria’, kutuk and rasi (a kind of magic animal). The meanings being interpreted are categorized into six categories. The interpretation of the physical vi symbols of the local wisdom has successfully interpreted nineteen symbols, they are long house, farm, the hut of paddy (dango padi), paddy, rice, the kids of leaves, sirih ( a kind of herbal leaf), farm hut (dango uma), paca’ basa’, hunted head (kepala kayau), weapon, agriculture, gasing, canoe, traditional food, forest, enggang (local bird), pig, mause, parakeet, as well as keto’, buria’, kutuk and rasi (a kind of magic animal). The meanings being interpreted are categorized into six categories. Firstly, the meaning is related to the belief heritage; secondly, it is related to tradition and custom; the third, it is related to identity; the fourth, it is related to the environment; the fifth, it is related to society way of life; and the sixth is the one related to creativity and technology. The interpretation of the spiritual symbols of local wisdom has also successfully interpreted sixteen symbols which cover the tradition of batalah, circumcisition, head hunting (mengayau), notokng, baliatn, marriage, divorce, Jubata, nyangahatn, magic power, loud cry (tariu), muafakat, solidarity, loyalty, friendship, and kinship. All the meanings interpreted are grouped into five catagories. The first is the meaning related to heritage belief; the second is related to tradition and custom, the third is the one related to the environment; the forth is related to the social way of life; the fifth is related to togetherness or sharedness (kemuafakatan).